Derrida and hospitality : theory and practice - Still, Judith 1958- (Edinburgh University Press, 2010)
Judith Still sets Derrida's work in a series of contexts in a series of contexts including the socio-political history of France, especially in relation to Algeria, and his relationship to other writers, most importantly Hélène Cixous and Emmanuel Levinas: key thinkers of hospitality. Working across the full breadth of fields that Derrida's work on hospitality influenced, Still thinks through relationships between individuals and the community or state. Judith Still also follows the thread of sexual difference in Derrida's writing to shed light on his exploration of the complex and delicate, strange yet familiar, political and ethical dilemmas of how to be those impossible things: a good host and a good guest